2009
DOI: 10.1038/ejcn.2009.136
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and metabolic syndrome in the elderly: results from the Italian longitudinal study on aging

Abstract: Background/Objectives: Although there is plenty of evidence of the association between metabolic syndrome (MS) and cardiovascular disease, the relationship between alcohol consumption and MS is still questioned. The few publications with respect to the elderly seem to indicate that alcohol consumption is unassociated with MS. The aim of this study was to assess the association between alcohol consumption and the prevalence and incidence of MS, as well as its components in a large sample of Italian elderly peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 46 publications
1
27
1
1
Order By: Relevance
“…14 As in those previous cross-sectional studies, several longitudinal studies on the association between alcohol consumption and the incidence of MetS in men also have reported discordant results. [19][20][21][22] Results from the Tromso study, 19 the elderly Italian longitudinal study, 20 and the British Regional Heart Study 21 showed that alcohol intake is not related to the incidence of the MetS, which is not consistent with our results. This could be attributable to differences in race and study design; the Tromso study 19 was only based on the frequency of alcohol consumption and included 3 types of beverage (beer, wine, and liquor); the Italian study 20 enrolled only the elderly.…”
Section: Discussioncontrasting
confidence: 56%
“…14 As in those previous cross-sectional studies, several longitudinal studies on the association between alcohol consumption and the incidence of MetS in men also have reported discordant results. [19][20][21][22] Results from the Tromso study, 19 the elderly Italian longitudinal study, 20 and the British Regional Heart Study 21 showed that alcohol intake is not related to the incidence of the MetS, which is not consistent with our results. This could be attributable to differences in race and study design; the Tromso study 19 was only based on the frequency of alcohol consumption and included 3 types of beverage (beer, wine, and liquor); the Italian study 20 enrolled only the elderly.…”
Section: Discussioncontrasting
confidence: 56%
“…Another far from negligible effect of alcohol has to do with its influence on insulin sensitivity and the incidence of diabetes. Alcohol consumption is associated with type 2 diabetes in a U-shaped fashion, indicating a lower risk of type 2 diabetes in moderate alcohol consumers than in abstainers or heavy drinkers, and this applies to older women too (26) . On the other hand, alcohol consumption has a harmful effect on systolic and diastolic blood pressure levels, which are risk factors for renal function, as amply demonstrated (27) .…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with the metabolic syndrome, a condition characterized by disturbed glucose and insulin metabolism, dyslipidemia, hypertension, and central obesity, are at greater risk of developing type 2 diabetes mellitus and cardiovascular disease, but there is evidence that alcohol intake is not related to the risk of metabolic syndrome in older people [59,60].…”
Section: Cardiovascular Disease and Other Conditionsmentioning
confidence: 99%